Clinical and histopathological responses to bee venom phonophoresis in treating venous and diabetic ulcers: a single-blind randomized controlled trial - Othman, Eman M.; Hamada, Hamada Ahmed; Mohamed, Ghada I.; Abdallah, Ghada A.; Ahmed, Zeinab S.; Al-Shenqiti, Abdullah M.; Kadry, Ahmed Mahmoud (Frontiers in Medicine, 2023)
Introduction Chronic venous and diabetic ulcers are hard to treat that cause patients long time of suffering as well as significant healthcare and financial costs. Purpose The conducted study was to evaluate the efficacy of bee venom (BV) phonophoresis on the healing of chronic unhealed venous and/or diabetic foot ulcers Also, to compare the healing rate of diabetic and venous ulcers. Methodology The study included 100 patients (71 males and 29 females) with an age range of 40-60 years' old who had chronic unhealed venous leg ulcers of grade I, grade II, or diabetic foot ulcers with type II diabetes mellitus. They randomly assigned into four equal groups of 25: Group A (diabetic foot ulcer study group) and group C (venous ulcer study group) who both received conservative treatment of medical ulcer care and phonophoresis with BV gel, in addition to group B (diabetic foot ulcer control group) and group D (venous ulcer control group) who both received conservative treatment of medical ulcer care and received ultrasound sessions only without BV gel. Wound surface area (WSA) and ulcer volume measurement (UVM) were used to assess the ulcer healing pre-application (P0), post-6 weeks of treatment (P1), and after 12 weeks of treatment (P2). In addition to Ki-67 immunohistochemistry was used to evaluate the cell proliferative in the granulation tissue of ulcers pre-application (P0) and after 12 weeks of treatment (P2) for all groups. Results This research revealed a statistical significance improvement (p ≤ 0.0) in the WSA, and UVM with no significant difference between study groups after treatment. Regarding Ki-67 immunohistochemistry showed higher post treatment values in the venous ulcer group in comparison to the diabetic foot ulcer group. Conclusion Bee venom (BV) provided by phonophoresis is effective adjuvant treatment in accelerating venous and diabetic foot ulcer healing with higher proliferative effect on venous ulcer. Clinical trial registration www.ClinicalTrials.gov, identifier: NCT05285930.